Implementación de un dispositivo IoMT de fisioterapia portátil para la asistencia en la rehabilitación de pacientes con esguinces de tobillo de primer y segundo grado en la Asociación de Personas con Discapacidad Física de Chimborazo (ASODICH). - Arizo Lara, Jeancarlos Patricio (2025)
This thesis presents the development of an IoMT (Internet of Medical Things) device for the rehabilitation of ankle sprains, aiming to improve traditional methods through a technological solution. The proposed system is portable, ergonomic, and adaptable to various environments, including hospitals, clinics, and homes, thereby facilitating access to therapy and ensuring continuity of care. The device features a mobile application that enables patients and therapists to control therapy with precision and ease. This app offers parameter customization, progress monitoring, and direct communication between users and professionals. For increased safety, the system includes an emergency stop mechanism. Open-source hardware and 3D printing were utilized, resulting in a functional and accessible design with potential for future enhancements. The implementation at ASODICH, along with the results of the t-test for unequal variances, revealed a significant difference in rehabilitation times. Patients who used the device experienced faster recovery compared to those who followed traditional methods, demonstrating its greater effectiveness.